Belgeler Işığında Osmanlı Eğitiminde Yeni Sistem Arayışları / Searching for New System in Ottoman Education in the Light of Documents - Yücedağ, İsmail and Erdoğan, Hamit (Journal of History Culture and Art Research, 2018)
ABSTRACT The aim of this study is to shed light on what is done in Ottoman education or to try to be done within the framework of structural changes and new system searches. Ottoman education, which constitutes the pre-Republic period of the Turkish education system and has an important position in terms of the Turkish educational history, gains importance in this respect. Considering the size of the Ottoman documents, it is observed that the school has an important place in terms of education, the contribution of the people to the schooling event and the quality of education is taken into consideration by taking precautions in line with the conditions of that period. It is seen that the existence of 500 Muslim households is a prerequisite for opening a secondary school in a settlement. Government efforts to encourage and encourage the public to contribute to education are similar to the present. In order to be able to teach the sciences such as Arabic, Persian, Mathematics and Geography in the best way to the students, all the expenses of the region’s people and keeping competent teachers can be considered as an effort to improve the quality of education. can be considered as an effort to improve the quality of education. A similar effort can be seen in teaching the new teaching methods to the teachers on the one hand and being paid all the expenses by the local people on the other. Mr. Dalıdereli Abdülkadir, who was assigned a salary of 400 kurus in one of the schools opened in Sofia, can be given as an example. It is noteworthy that civilization will be possible with the spread of science and education all over the country, and that the state will endeavor to do all material and spiritual work for this to happen. If necessary, education materials imported from abroad will be exempt from tax. In this context, in accordance with the decision taken by the Education Council, the 3,500 maps which are produced in Europe for secondary schools were exempt from tax. The lack of loyalty and communication in the centrality and provincial relations in the central management system emerges as one of the most important problems of that period. ÖZ Bu çalışmanın amacı, yapısal boyuttaki değişim ve yeni sistem arayışları çerçevesinde Osmanlı eğitiminde nelerin yapıldığı ya da yapılmaya çalışıldığına belgeler doğrultusunda ışık tutmaktır. Günümüz Türk eğitim sisteminin de Cumhuriyet öncesi dönemini oluşturan ve Türk eğitim tarihi boyutu bakımından önemli bir konuma sahip bulunan Osmanlı eğitimi bu açıdan önem kazanmaktadır. Konuya Osmanlı belgeleri boyutundan bakıldığında, günümüzde de eğitim felsefesi açısından önemli bir yeri olan okullaşma, halkın okullaşma olayına katkı sunması, eğitimin kalitesi gibi hususlara o dönemin koşullarına uygun tedbirler alınarak gerekli önemin verilmeye çalışıldığı gözlemlenmektedir. Bir yerleşim yerinde Rüştiye mektebinin açılabilmesi için 500 Müslüman hane bulunmasının ön koşul olarak belirlendiği görülmektedir. Halkın eğitime katkıda bulunmasını sağlamak amacıyla devlet tarafından yönlendirilmesi ve teşvik edilmesi çalışmaları günümüze benzer şekilde o dönemde de mevcuttur. Arapça, Farsça, Matematik, Coğrafya gibi bilimlerin öğrencilere en iyi şekilde öğretilebilmesi için bütün masrafları bölge halkı tarafından karşılanarak dışarıdan yetkin öğretmenlerin tutulması, eğitimin kalitesini artırma çabası olarak değerlendirilebilir. Benzer bir çaba yine tüm masrafları yöre halkının karşılamasıyla bir yandan yeni öğretim usullerini öğretmenlere öğretmek diğer yandan da öğrencilere ders verme amacıyla dışarıdan yetkin hocaların görevlendirilmesinde görülmektedir. Sofya’da açılan iptidai okullardan birinde 400 kuruş maaşla görevlendirilen Darıdereli Abdülkadir Efendi bu konuya örnek olarak verilebilir. Medeniyetin, ilim ve eğitimin memleketin her tarafına yayılması ile mümkün olacağı ve bunun gerçekleşmesi için devletin maddi ve manevi tüm çalışmaları yapmaya gayret edeceği vurgusu dikkat çekicidir. Gerekirse yurt dışından ithal edilen eğitim araç-gereçleri vergiden muaf tutulacaktır. Bu bağlamda Maarif Meclisince alınan karar doğrultusunda Rüştiye mektepleri için Avrupa’da imal ettirilerek getirtilen 3.500 harita vergiden muaf tutulmuştur. Merkez-taşra ilişkilerinde merkezi yönetim sisteminden kaynaklanan hantallık ve iletişim eksikliği, o dönemin de önemli sorunlarından biri olarak karşımıza çıkmaktadır.